Contextual Meaning Study of Translation of Childrenâ€™s Story â€œThe Lion Kingâ€ from English into Indonesian - Suprapto, Djuria (Lingua Cultura, 2010)
Article aimed to present study on the translation of words, phrases, expressions and sentences in a children's story.The story of "The Lion King" was used as case and content analysis was applied as a reference for the study. The focus of this analysis was aimed to observe the appearance of the terms or meaning of certain words that are considered important and supports the goals of the research, in this case is the translation of words, phrases, sentences in the source language (English) into the target language (Indonesian). As its criterion, dictionaries was used and rules of contextual translation was applied. It can be concluded that children's stories emphasize the style and meaning contained in it, so the translation is done must consider the context of the story.Â